D-DI/PLT can be a prognostic indicator for sepsis - Zhao,Xiaojun; Wu,Xiuhua; Si,Yi; Xie,Jiangang; Wang,Linxiao; Liu,Shanshou; Duan,Chujun; Wang,Qianmei; Wu,Dan; Wang,Yifan; Chen,Jijun; Yang,Jing; et al. (PeerJ, 2023)
Aims To investigate the indicators affecting the early outcome of patients with sepsis and to explore its prognostic efficacy for sepsis. Methods We collected clinical data from 201 patients with sepsis admitted to the emergency department of Xijing Hospital between June 2019 and June 2022. The patients were categorized into groups (survival or fatality) based on their 28-day prognosis. The clinical characteristics, biochemical indexes, organ function-related indicators, and disease scores of the patients were analyzed for both groups. Risk factor analysis was conducted for the indicators with significant differences. Results Among the indicators with significant differences between the deceased and survival groups, D-dimer (D-DI), Sequential Organ Failure Assessment (SOFA) score, platelet (PLT), international normalized ratio (INR), and D-DI/PLT were identified as independent risk factors affecting the prognosis of sepsis patients. Receiver operating characteristic (ROC) curves showed that D-DI/PLT (area under the curve (AUC) = 93.9), D-DI (AUC = 89.6), PLT (AUC = 81.3), and SOFA (AUC = 78.4) had good judgment efficacy. Further, Kaplan Meier (K-M) survival analysis indicated that the 28-day survival rates of sepsis patients were significantly decreased when they had high levels of D-DI/PLT, D-DI, and SOFA as well as low PLTs. The hazard ratio (HR) of D-DI/PLT between the two groups was the largest (HR = 16.19). Conclusions D-DI/PLT may be an independent risk factor for poor prognosis in sepsis as well as a clinical predictor of patient prognosis.
Keywords: Sepsis; Human; Prognosis; D-DI/PLT; ROC curve; Risk factor